2023
DOI: 10.3390/cryst13071032
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Investigation of the Diffusion of TM and the Nucleation and Growth of L12 Al3TM Particles in Al Alloys

Abstract: The key parameters of growth and nucleation of Al3TM particles (TM = Sc-Zn, Y-Cd and Hf-Hg) have been calculated using the combination of the first principles calculations with the quasi-harmonic approximation (QHA). Herein, the diffusion rate Ds of TM elements in Al is calculated using the diffusion activation energy Q, and the results show that the Ds of all impurity atoms increases logarithmically with the increase in temperature. With the increase in atomic number of TM, the Ds of 3–5d TM elements decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…T. Hu et al [25] describe the diffusion of TM and the nucleation and growth of particles in Al alloys based on first principles.…”
Section: Contributionsmentioning
confidence: 99%
“…T. Hu et al [25] describe the diffusion of TM and the nucleation and growth of particles in Al alloys based on first principles.…”
Section: Contributionsmentioning
confidence: 99%
“…There is an extensive body of literature on diffusion processes in various types of macroscopic, coarsely crystalline structures [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Although experimental methods were difficult to investigate atomic diffusion in intermetallic compounds [ 19 , 20 ], first-principles calculations can provide new insights into the microscopic mechanisms of atomic diffusion [ 18 , 20 ]. First-principles calculations by Fan [ 21 , 22 ] showed that with the increase of the atomic number, the diffusion rate of rare-earth elements increased from Sc to Y, La, and then decreased to Lu. Shi et al [ 23 ] investigated the atomic diffusion of pure and transition-element (TM)-doped L1 2 -Al 3 Sc based on first principles and found that under a strong Al-rich condition, the V Sc defect obtained low formation energy and the NNJ mechanism mediated by V Al was most favorable for Sc atomic diffusion.…”
Section: Introductionmentioning
confidence: 99%